Analisis Perbandingan Kualitas Aplikasi E-Wallet Berdasarkan Pengalaman Pengguna Menggunakan Metode User Experience Questioner (UEQ) - Alam, Alji Ridwan Syah; Rahmawita, Medyantiwi; Megawati, Megawati; Fronita, Mona (Program Studi Teknik Informatika Universitas Pamulang, 2024)
With technological advances, payments that originally used cash have now switched to digital money via digital wallets. In 2023, Go-Pay and OVO will become leaders in the e-wallet market. In this fierce competition, users experience various problems. This research aims to analyze and compare user experiences in the two applications using the User Experience Questionnaire (UEQ) method. The UEQ questionnaire has 26 question items distributed to 100 Go-Pay and OVO users in Pekanbaru. The results of the two applications found significant differences on several average (mean) scales, such as Efficiency, Stimulation, and Novelty. In contrast, on the Attractiveness, Perspicuity, and Dependability variables there were not very significant differences in the average (mean), but still, the application OVO requires more improvement in every aspect of the scale because when compared to the Go-Pay application, the OVO application still shows differences on the UEQ scale. Keywords: Analysis; Technology; Digital Wallet; User Experience; User Experience Questionnaire